Pedagogical Competence of Indonesian Language Lecturers at Universitas Buana Perjuangan Karawang - Repelita, Tridays; Hidayat, Sholeh; Anriani, Nurul; Prihamdani, Depi; Nugraha, Yogi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study aims to analyse the pedagogical competence of Indonesian language lecturers at the Universitas Buana Perjuangan Karawang. The research method used in this study is qualitative descriptive, with techniques including observation, documentation, portfolio analysis, student feedback, and performance evaluation. The assessment focused on the mastery of teaching media and technology, the ability to prepare teaching materials, the development of teaching content, the ability to manage teaching materials, and the ability to assess student performance. Based on the analysis results, it can be concluded that the pedagogical competence of Indonesian language lecturers at the Universitas Buana Perjuangan Karawang is considered good.